0
$\begingroup$

I need to find Laurent expansion for $$\frac{e^{\frac{1}{z-1}}}{z(z+1)}$$ about $z=1$ for $1 \lt |z-1| \lt 2$.

I've tried to solve this as it was suggested in the book: find Laurent expansion for $f_1(z) = \frac{1}{z+1}$ about $z=1$ for $|z-1| \lt 2$ and Taylor expansion for $f_2(z) = \frac{e^{\frac{1}{z-1}}}{z}$ for $|z-1| > 1$ (this function is analytic in this area, so Taylor series is equal to Laurent series) and then multiply them.

I get $\frac{1}{z+1} = \sum_{n=-\infty}^{-1}(-1)^{n-1}2^{-n-1}(z-1)^n$, $\frac{1}{z} = \sum_{n=0}^{\infty}(-1)^n(z-1)^n$ and $e^{\frac{1}{z-1}} = 1+ \sum_{n=1}^{\infty}\frac{1}{n!(z-1)^n}$.

But I don't understand how can I find product of these series?

Thanks for your help.

$\endgroup$
1
$\begingroup$

Hint: With $z=u+1$ $$\dfrac{1}{z(1+z)}=\dfrac{1}{1+u}-\dfrac{\frac12}{1+\frac{u}{2}}=\sum_{n=0}(-u)^n-\dfrac12\sum_{n=0}(-\frac{u}{2})^n=\dfrac{1}{2}-\dfrac{3}{4}u+\dfrac{7}{8}u^2-\dfrac{15}{16}u^3+\cdots$$ now find the product of this series and the series of $e^{\frac{1}{u}}$ and substitute $u=z-1$.

$\endgroup$
  • $\begingroup$ Why do we make the substitution z=u+1? $\endgroup$ – blargen Apr 12 at 17:41
  • $\begingroup$ @blargen Just for simplifying the calculations. $\endgroup$ – Nosrati Apr 12 at 18:35

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.